Concrete floors and slabs proceedings of the international seminar held at the University of Dundee, Scotland, UK on 5-6 September 2002 - Dhir, Ravindra K.; Newlands, Moray D.; Harrison, T. A. (Thomas Telford, 2002)
There is no substitute for concrete that can be used on the same engineering scale. Its sustainability, exploitation and further development are necessary for a healthy economy and environment worldwide. Concrete must keep evolving to satisfy the increasing demands of all its users.